P‐65: Photobiological Safety Classification and Measurement for Electronic Display Devices. Issue 1 (May 2016) - Qiao, Bo; Mou, Xi; Mou, Tongsheng
Abstract : Currently, photobiological safety of electronic display devices is highly concerned by product manufacturers. The right risk group classifications for certain products are likely not easy, because many factors will affect the measurement of quantities relating to optical radiation hazards and led to high uncertainty. How to measure the photobiological safety of electronic display devices and what are main factors in the safety assessment, are the topics in this study.